Pemberdayaan Pendidikan Melalui Pengadaan Buku Bacaan Perpustakaan Desa Jatimulya, Kuningan, Untuk Masa Depan Yang Unggul - Agustiana, Vina; Nugroho, Muhammad Aprianto Budie; Oktoma, Erwin; Muawanah, Aam; Yasmin, Alifia; Ramanda, Arfan; Aldy, Elgah; Azka, Fina Saeila; Saputra, Nico; Rafika (Yayasan Kajian Riset dan Pengembangan RADISI, 2024)
The low levels of literacy and numeracy in Indonesian villages present significant challenges to social and economic development. Village libraries, which should serve as literacy hubs, often lack sufficient book collections to support community education. This community service activity aims to enhance literacy in Jatimulya village, Kuningan, West Java through the provision of reading materials and the organization of the village library. The methods used include setting up a reading garden, distributing books, and conducting literacy activities. The activity was attended by 18 elementary school students who showed high enthusiasm during storytelling sessions and reading exercises. The results indicate that appropriate book provision and literacy programs can increase students' reading interest and literacy skills. With better library facilities and ongoing support, village libraries have great potential to become effective literacy centers that support educational empowerment in rural areas. This activity successfully achieved its goals and had a positive impact on the community, particularly in fostering a literacy culture among children.